2005
DOI: 10.1016/j.ejheart.2005.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined administration of low dose atorvastatin and vitamin E on inflammatory markers and endothelial function in patients with heart failure

Abstract: Background: Heart failure has been associated with impaired endothelial function, increased inflammatory process and elevated oxidative stress status. Both statins and vitamin E separately improve endothelial function in patients with hypercholesterolemia and/or advanced atherosclerosis. Aim: To evaluate the effect of atorvastatin alone or in combination with vitamin E on endothelial function and serum levels of interleukin-6 (IL-6), tumor necrosis factor alpha (TNF-a) and vascular cells adhesion molecule (sVC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 51 publications
1
60
0
5
Order By: Relevance
“…Sola et al [175] found that administration of atorvastatin improved left ventricular ejection fraction and attenuated adverse left ventricular remodeling in patients with nonischemic heart failure. Atorvastatin also dampened the inflammatory process in patients with heart failure [176] . In a rat model of post-myocardial infarction- [177] .…”
Section: Endoplasmic Reticulum Stress Is Involved In the Development mentioning
confidence: 94%
“…Sola et al [175] found that administration of atorvastatin improved left ventricular ejection fraction and attenuated adverse left ventricular remodeling in patients with nonischemic heart failure. Atorvastatin also dampened the inflammatory process in patients with heart failure [176] . In a rat model of post-myocardial infarction- [177] .…”
Section: Endoplasmic Reticulum Stress Is Involved In the Development mentioning
confidence: 94%
“…Patients treated with simvastatin, niacin and a combination of different antioxidants (400 IU bis in die (BID; twice a day) vitamin E, 500 mg BID vitamin C, 12.5 mg BID β-carotene and 50 mg BID selenium) profited less than the simvastatin and niacin groups as the protective increase in HDL2 with simvastatin plus niacin was attenuated by concurrent therapy with antioxidants [243,244] . Tousoulis et al [245] treated patients suffering from ischemic heart failure with low dose atorvastatin (10 mg/d) alone or in combination with 400 IU/d vitamin E and found that vitamin E impairs the positive effects of atorvastatin, on, for example, endothelial function or inflammatory response. Many studies focusing on the effects of statins on human lipid levels also analyzed other plasma parameters, such as vitamin E status.…”
Section: Interactions With Pharmaceuticsmentioning
confidence: 99%
“…In patients with ischemic cardiomyopathy (40% with diabetes), atorvastatin (10mg/day) significantly improved post-ischemic FABF, but this effect was blunted by the co-administration of vitamin E (400 IU/day) [231]. Given the potential for statins to inhibit the cellular synthesis of plasma CoQ 10 , a by-product of isoprenoid metabolism, their full benefit on improving endothelial function may be blunted [232,233].…”
Section: Combination Therapiesmentioning
confidence: 99%